Revealing Phytopharmaceutical Insights into Jaras Gambo Extract from Uncaria gambir Roxb. against Breast Cancer Using Network Pharmacology and ADME/Tox Approach - Viviani, Rafiqah Nur; Mahendra, Nathasya Shasykirana; Shiyan, Shaum; Pratiwi, Galih (Jurnal Ilmiah Medicamento, 2026)
Background: Breast cancer remains a leading cause of mortality in women and demands multi-target strategies that can address pathway redundancy and resistance.Objective: This study aimed to characterize the bioactive constituents of Jaras Gambo Toman extract and evaluate its potential anti-breast cancer activity through an integrated network pharmacology and molecular docking approach.Methods: Jaras Gambo (processed gambier sap mass; Uncaria gambir Roxb.) collected in Babat Toman, South Sumatra, was macerated in ethanol, and the macerate was then filtered and concentrated to obtain a crude extract. Its constituents were profiled by liquid chromatography–high-resolution mass spectrometry (LC–HRMS). Network pharmacology (target prediction, pathway enrichment, and drug-likeness/toxicity screening) was integrated with structure-based molecular docking to prioritize active constituents and predict their interactions with breast cancer–related proteins.Results: The results of the analysis show therapeutic potential through the significant binding affinity between the bioactive components of the extract and proteins in the regulation of cancer cell proliferation and apoptosis, particularly AKT1, TP53, BCL2, TNF, and EGFR. Molecular interactions are suggested by favorable binding affinity parameters accompanied by the formation of hydrogen and hydrophobic bonds at the active sites of key residues. The involvement of several signaling pathways, such as the PI3K/AKT pathway, p53 signaling pathway, and TNF signaling pathway, may represent key mechanistic pathways of bioactive compounds in targeting disease proteins. Further characterization showed that there are eight main active components, including chlorogenic acid, isoquercitrin, morin hydrate, naringenin, quercetin, eriodictyol, ribofuranoside, and scopoletin, which showed docking profiles comparable to erlotinib across selected targets.Conclusion: These results suggest the potential of Jaras Gambo Toman extract as a potential source of multi-target bioactive compounds for further breast cancer research.